Challenges and Solutions for AI in Cloud Computing : A Technical Analysis - Sanjeev Kumar Pellikoduku (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the critical intersection of Artificial Intelligence and cloud computing, examining the transformative impact of their integration across various industries. The research presents a comprehensive analysis of key challenges faced by organizations implementing AI in cloud environments, including security concerns, operational complexities, and ethical considerations. The study investigates solutions for data privacy protection, model security, integration complexity, and performance monitoring while addressing bias, fairness, and explainability in AI systems. Through extensive analysis of real-world implementations and industry research, this paper provides practical frameworks and evidence-based solutions for organizations at different stages of their AI cloud integration journey. The findings demonstrate significant improvements in operational efficiency, cost reduction, and system performance when appropriate strategies are implemented, while highlighting the importance of ethical considerations and governance frameworks in ensuring sustainable AI deployment in cloud environments.